SCREENING ON CATARACT APPLICATION (SERIOC): Poster Presentation - Observational Study - Ophthalmologist - Wulansari, Sriana; Sungkono, Henry Santosa; Akbar, Muhamad Hassanul (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : West Nusa Tenggara is a province that has the second highest prevalence of blindness at the national level according to the results of the 2014 Rapid Assessment of Avoidable Blindness (RAAB) survey. During the covid-19 period the offline cataract screening is not permitted, as a result it’s difficult to reach underprivileged and isolated areas, also people with disabilities. In 2021 West Nusa Tenggara Eye Hospital launched a smartphone-based eye health examination application Screening On Cataract namely SERIOC, while still paying attention to service standards clinically and in management. SERIOC can be used by public health as the nearest public health facility. Methods : The waterfall method is used in the development of this application, The waterfall methodology is a project management approach that emphasizes a linear progression from beginning to end of a project. This methodology, is front-loaded to rely on careful planning, detailed documentation, and consecutive execution. Results : SERIOC has successfully screened 2,713 patients from 2021 with 2117 patients diagnosed cataract and 593 patients diagnosed non-cataract whose data is centralized and directly connected to an ophthalmologist at the West Nusa Tenggara Eye Hospital. Patients diagnosed with cataracts will be referred to the hospital for further action. Conclusion : Based on the information above, it can be concluded that SERIOC application in eye health screening is very effective and efficient method to avoid blindness on West Nusa Tenggara.